The Contribution Of Fintech Innovation To Expanding Financial Inclusion In Developing Countries – Algeria As A Case Study - Donia, Morsli; Meriem, BOUKABOUS (Journal of Ecohumanism, 2025)
This study aims to assess the impact of financial technology (FinTech) on enhancing financial inclusion in Algeria, an emerging economy facing structural challenges in integrating unbanked populations into the formal financial system. The research adopts a mixed descriptive–evaluative methodology that combines quantitative analysis of financial inclusion indicators (such as bank account ownership rates, digital wallet penetration, and the volume of electronic transactions). The findings reveal that the adoption of digital financial solutions in Algeria has contributed to increasing the proportion of individuals integrated into the formal financial system and to improving access to financial services, particularly in rural and low-income areas. The analysis highlights that mobile-based services, electronic wallets, and digital payment systems have been among the most influential drivers in integrating large segments of the population. However, the results also indicate the presence of regulatory and technological infrastructure constraints that limit the full potential of FinTech, including low levels of financial literacy, trust-related challenges in digital platforms, and regulatory compliance processes. The study concludes that effective collaboration among regulatory authorities, FinTech institutions, and the traditional banking sector is essential to maximize the impact of financial innovation on financial inclusion.